An overview of the oil palm empty fruit bunch (OPEFB) potential as reinforcing fibre in polymer composite for energy absorption applications - Abd Rahman, Mohd Khairul Faizi; Abu Bakar, Shahriman; Abdul Majid, Mohd Shukry; Mohd Tamrin, Shamsul Bahri; Ng, Yee Guan; Basah, Shafriza Nisha; Cheng, Ee Meng; Rojan, Mohd Afendi; Mohamad Razlan, Zuradzman; Wan Ahmad, Wan Khairunizam; Desa, Hazry (EDP Sciences, 2016)
The oil palm empty fruit bunch (OPEFB) natural fibres were comprehensively reviewed to assess their potential as reinforcing materials in polymer composites for energy absorption during low-velocity impact. The typical oil palm wastes include trunks, fronds, kernel shells, and empty fruit bunches. This has a tendency to burden the industry players with disposal difficulties and escalates the operating cost. Thus, there are several initiatives have been employed to convert these wastes into value added products. The objective of this study is to review the potential of oil palm empty fruit bunch (OPEFB) as natural fibre polymer composite reinforcement to absorb the energy during low-velocity impact as another option for value added products. Initially, this paper reviewed the local oil palm waste issues. Previous research works on OPEFB polymer composite, and their mechanical characterization is appraised. Their potential for energy absorption in low-velocity impact application was also elaborated. The review suggests high potential applications of OPEFB as reinforcing materials in composite structures. Furthermore, it is wisely to utilize the oil palm biomass waste into a beneficial composite, hence, promotes the green environment.